Alasan Gaya Hidup Konsumen dalam Mengkonsumsi Kebaya sebagai Barang Mewah - Annisa, Renny; Rohman, Fatchur; Noermijati (Jurnal Aplikasi Manajemen, 2014)
The aim of this research is to explore digger concerning to the reason of consumer's lifestyle on consuming party kebaya as a luxurious product on women consumers at Channisa Boutique Malang. This research uses Qualitative Approach with phenomenology research design in order to explore digger concerning to the the partisipats'experiences and reasons towards the lifestyle such as buying and using kebaya as a luxurious product. The data was taken by interviewing in depth of 5 informers who are customers of Channisa Boutique as partisipants. The data analysis is using coding technique in order to make easier on the meaning formulation process of the deep interview results. The result of this research shows: the reasons in which being a background of consumer's lifestyle, there are:1) the role of reference group 2) achievement motivation 3) self-confident 4) self image. The implication of the research towards marketers are they may give more attention to the customers'reference group vision, the equation of perception with the customers'fashion trend vision, customers'self confidence and self image. The originality of this research is that, it brings attention to the consumer's experiences and reasons towards a lifestyle on the consumption of Indonesian local luxury fashion product named party kebaya.